Effects of Renal Impairment on the Pharmacokinetics of the Dual GIP and GLP-1 Receptor Agonist Tirzepatide - Urva, Shweta; Quinlan, Tonya; Landry, John; Martin, Jennifer; Loghin, Corina (Clinical pharmacokinetics, 2021)
Background and Aims The pharmacokinetics (PK) and single-dose tolerability of tirzepatide, a dual glucose-dependent insulinotropic polypeptide and glucagon-like peptide-1 receptor agonist being developed for once-weekly treatment of type 2 diabetes (T2D), weight management, and nonalcoholic steatohepatitis, was evaluated in subjects with renal impairment versus healthy subjects with normal renal function. Methods Forty-five subjects, categorized by baseline renal status, i.e. mild ( n = 8, estimated glomerular filtration rate [eGFR] 60–89 mL/min/1.73m 2 ), moderate ( n = 8, eGFR 30–59 mL/min/1.73m 2 ), severe renal impairment ( n = 7, eGFR < 30 mL/min/1.73m 2 ), end-stage renal disease requiring dialysis ( n = 8), and normal renal function ( n = 14, eGFR ≥ 90 mL/min/1.73m 2 ), received a single subcutaneous dose of tirzepatide 5 mg. Tirzepatide plasma concentrations up to 648 h postdose were measured to compute PK parameters. The primary analysis evaluated the ratios of area under the plasma concentration–time curves (AUCs) and maximum plasma drug concentration ( C max ) of renal impairment versus the normal renal function group (90% confidence interval [CI]). In addition, the relationship between PK parameters and continuous variables of renal function was assessed by linear regression. Results Tirzepatide exposure was similar across renal impairment groups and healthy subjects. The 90% CI of ratios of AUCs and C max comparing each renal impairment group versus normal renal function spanned unity, except for a 25–29% increase in AUCs in the moderate renal impairment group. There was no significant relationship between tirzepatide exposure and eGFR. Few adverse events were reported across the renal impairment and normal renal function groups. The majority were mild in severity and of a gastrointestinal nature in the renal impairment groups. Conclusion There were no clinically relevant effects of renal impairment on tirzepatide PK. Dose adjustment may not be required for patients with renal impairment. Clinical Trial Registration ClinicalTrials.gov NCT03482024.